Effect of High Temperature Heating on Chemical Compounds in Magnesium Composite Materials - Ruzuqi, Rezza; Maryanto, Eko Tavip (Journal of Applied Engineering and Technological Science (JAETS), 2024)
The development of magnesium composite-based seawater battery anode technology is actively pursued, especially in its ability to transmit and store electrical energy. However, many overlook the possibility that significant temperature changes during the process may lead to chemical compound alterations, potentially affecting the battery's performance. Therefore, this research examines the changes in chemical compounds in magnesium composite-based seawater battery anodes caused by high temperatures. In this study, the synthesis process of magnesium composite material composed of MgAlSnMn with variations of Manganese (wt.-%) 14.8, 15, 15.2, 15.4, 15.6. Then it was milled for 60 minutes. Next, the materials were pelletized using a manual compacting machine with a diameter and compressive strength of 10 mm and 150 kg/cm2 respectively. After that, all materials were sintered at 7500C with a muffle furnace for 60 minutes. In this study, XRD equipment was utilized to determine chemical compound changes. The results indicate that magnesium composite materials undergo significant chemical compound alterations at high temperatures, including MgO (Magnesium Oxide Periclase), Al18Mg3Mn2, and the remaining Al elements. This could potentially disrupt the performance of seawater batteries when applied. It is hoped that further research will be conducted in the future to enhance the quality and performance of the product.